2013
DOI: 10.4012/dmj.2012-200
|View full text |Cite
|
Sign up to set email alerts
|

Micro-shear bond strength of adhesive resins to enamel at different relative humidity conditions

Abstract: This study tested whether exhaled humid conditions would affect the adhesion of etch-and-rinse, two-step and one-step self-etch adhesive resins to enamel. Enamel surfaces of human maxillary anterior teeth (N=240, n=20) were exposed to four humid conditions (H1: 63-68%, H2: 73-78%, H3: 93-98%, H4: 36-45% RH) during bonding with Adper Single Bond 2 (SB2), Clearfil SE Bond (CSE) and Adper Easy Bond (AEB). Specimens were stored in distilled water at 37ºC for 24 h and tested to failure using micro-shear bond streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
1
10
2
1
Order By: Relevance
“…However, the reproducibility of testing results is affected by various factors regarding the inherent weakness of test institute [3]. Although ISO 11405 [23] strictly stresses that "a limitation of the bonding area is important," in most μ-SBS tests, the step of restricting the area of both the adhesive and the resin was often ignored [22,[24][25][26][27], and only the area of the resin cylinder was taken as the bonding area to calculate the bond strength of tested materials. Therefore, the objective of this study was to compare the bond quality of different adhesive systems by employing the μ-SBS test with and without adhesive area restriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reproducibility of testing results is affected by various factors regarding the inherent weakness of test institute [3]. Although ISO 11405 [23] strictly stresses that "a limitation of the bonding area is important," in most μ-SBS tests, the step of restricting the area of both the adhesive and the resin was often ignored [22,[24][25][26][27], and only the area of the resin cylinder was taken as the bonding area to calculate the bond strength of tested materials. Therefore, the objective of this study was to compare the bond quality of different adhesive systems by employing the μ-SBS test with and without adhesive area restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the adhesive property of the different adhesives can be distinguished with Method I (Figure 2), but this is not the case for Method II. In most traditional μ-SBS tests [12,13,22,[24][25][26][27], the area of the resin cylinder was taken as the bonding area to calculate the bond strength of the tested materials. Therefore, the higher nominal bond strength was obtained and only if massive improvement in bond quality can be distinguished with method II.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Total-etch adhesive and two-step self-etch adhesive resin exhibit significantly higher microshear bond strengths than that of one-step self-etch adhesive resin to enamel in all humidity conditions. [23] McLeod et al observed that the total-etch systems showed significantly higher shear bond strength to enamel than those of self-etch systems, [25] while Nazari et al [22] have put forward the superiority of the bond strength of the total-etch adhesive to one-step self-etch adhesive on both intact and ground enamel surfaces.…”
Section: Discussionmentioning
confidence: 97%
“…[21] In the light of these data, our results also sustain the Nazari 2012 suggestion that pre-etching prior to application of the self-etch adhesive can provide an effective bonding and grinding the surface may not be necessary. [22] The practitioners must take into account all these data, considering the oral cavity conditions, where humidity may decrease the adhesion quality to enamel and dentin [23] in order to choose the best technical solutions for each clinical case.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, não devem apresentar força de adesão muito superior a esses valores, pois isso pode ocasionar fraturas do esmalte durante a remoção dos bráquetes (Reynolds, 1975;Yamamoto et al, 2006;Prietsch et al, 2007;Holberg et al, 2014;Dumbryte et al, 2018). Paralelamente, na área da Odontologia, vários autores relataram que o condicionamento ácido associado à utilização de adesivos e compósitos, promove uma maior resistência ao cisalhamento (Årtun e Bergland, 1984;Knox et al, 2001;Han et al, 2007;Hikita et al, 2007;Luhrs et al, 2010;Demirtas et al, 2015;Jurišić et al, 2015) e ao microcisalhamento (Shimada et al, 2002;Nagayassu et al, 2011;Bavbek et al, 2013;Rosa et al, 2015;Kavitha et al, 2016;Righi et al, 2018).…”
Section: Introductionunclassified